The Role of Islamic Values in Enhancing The Effectiveness of English Language Teaching - Amanda Azzahra; Athaya Dwi Insyra; Kalayo Hasibuan (English Education Study Program Faculty of Teacher Training and Education, 2025)
This study investigates the integration of Islamic values into English Language Teaching (ELT) in Indonesian Islamic secondary schools, focusing on its impact on students’ academic performance, character development, and intercultural competencies. In Muslim-majority settings, the introduction of English can raise concerns over potential conflicts between Western values and Islamic principles. To address these concerns, a culturally responsive approach, incorporating Islamic values such as adab (ethical conduct), ihsan (excellence), ikhlas (sincerity), and ta'awun (cooperation), can harmonize global education demands with local religious and cultural beliefs. A qualitative research design, utilizing semi-structured interviews, classroom observations, and document analysis, was employed to gather comprehensive data from English language teachers and classroom settings. The findings indicate that integrating Islamic values into ELT not only enhances students' language proficiency but also promotes moral development and intercultural understanding. By using Islamic texts such as Qur’anic verses and Hadith in lessons, teachers create a learning environment that is both academically enriching and spiritually grounding. This approach not only fosters a deeper understanding of the English language but also prepares students to engage with the globalized world while maintaining their cultural and religious identity. The study contributes to the development of a values-based pedagogy in ELT, which can offer a balanced approach to academic and moral education in Muslim-majority contexts.